Impact of Z chromosome inversions on gene expression in testis and liver tissues in the zebra finch - Viitaniemi, Heidi M; Leder, Erica H; Kauzál, Ondřej; Stopková, Romana; Stopka, Pavel; Lifjeld, Jan T; Albrecht, Tomáš (Molecular ecology, 2024)
Chromosomal inversions have been identified in many natural populations and can be responsible for novel traits and rapid adaptation. In zebra finch, a large region on the Z chromosome has been subject to multiple inversions, which have pleiotropic effects on multiple traits but especially on sperm phenotypes, such as midpiece and flagellum length. To understand the effect, the Z inversion has on these traits, we examined testis and liver transcriptomes of young males at different maturation times. We compared gene expression differences among three inversion karyotypes: AA, B*B* and AB*, where B* denotes the inverted regions on Z with respect to A. In testis, 794 differentially expressed genes were found and most of them were located on chromosome Z. They were functionally enriched for sperm-related traits. We also identified clusters of co-expressed genes that matched with the inversion-related sperm phenotypes. In liver, there were some enriched functions and some overrepresentation on chromosome Z with similar location as in testis. In both tissues, the overrepresented genes were located near the distal end of Z but also in the middle of the chromosome. For the heterokaryotype, we observed several genes with one allele being dominantly expressed, similar to expression patterns in one or the other homokaryotype. This was confirmed with SNPs for three genes, and interestingly one gene, DMGDH, had allele-specific expression originating mainly from one inversion haplotype in the testis, yet both inversion haplotypes were expressed equally in the liver. This karyotype-specific difference in tissue-specific expression suggests a pleiotropic effect of the inversion and thus suggests a mechanism for divergent phenotypic effects resulting from an inversion.
Keywords: Liver; Animals; Phenotype; Finches; játra; spermie; Testis; Spermatozoa; pěnkavovití; Taeniopygia guttata; testis; liver; karyotyp; transcriptomics; pohlavní chromozomy; Chromosome Inversion; Male; chromosome inversion; Sex Chromosomes; Karyotype; exprese genu; transkriptom; fenotyp; mužské pohlaví; zvířata; Transcriptome; chromozomální inverze; Gene Expression